Photocatalytic Defluoroalkylation of Trifluoroacetates with Alkenes using 4-(Acetamido)thiophenol - Liu, Can; Shen, Ni; Shang, Rui (Synthesis, 2023)
Under mild irradiation conditions using violet light-emitting diodes, a catalytic amount of a thiolate of N-(4-mercaptophenyl)pivalamide promotes monoselective defluoroalkylation of trifluoroacetates with a variety of aliphatic alkenes in the presence of a formate salt. The reactions allow facile and low-cost synthesis of valuable α,α-difluoro substituted aliphatic carboxylate esters under mild conditions, and demonstrate the dual-functional role of arenethiolates in photocatalysis as both a strong photoreductant in a redox cycle and a hydrogen-atom-transfer catalyst.
Keywords: defluoroalkylation; trifluoroacetate; arenethiolate; dual function catalysts; photoredox catalysis; HAT catalysis